(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the issue of forming methods of general mathematical activity of students, which is an important part of the implementation of the thesaurus approach in teaching mathematics. When teaching mathematics at school and university, the question of the systemic formation of general mathematical methods of activity is practically not considered. The formation of general mathematical methods of activity, in particular methods of cognition (analysis, synthesis, abstraction, generalization, concretization) is the basis for the assimilation of new concepts, their properties, relationships between concepts, methods for solving problems. This helps to realize the developing potential of mathematics. Therefore, it is important to study the formation of these techniques in the process of teaching mathematics. The purpose of the study is to describe the model of formation of general mathematical methods of activity in the process of teaching mathematics. Research methods: empirical methods (observation of classes in schools and universities, interviews with teachers); analysis, synthesis, generalization, concretization from general scientific methods. Research results: a four-stage model for the formation of general mathematical methods of activity has been developed, a characteristic has been given to each stage. Conclusions. The process of forming methods of general mathematical activity can be carried out in the following stages: the formation of an understanding of the method, the interpretation of the given data (the implementation of the method on a specific example), the application of the method and its transfer. to a new situation. In accordance with this model, four stages were identified: preparatory, educational, reinforcing and practical. The process of formation can be used in the form of an educational map based on the definition of the type of activity, which is a special type of mental activity.